Sleep deprivation impacts the immunological milieu of epididymis leading to low sperm quality in rats - Zhean Li; Shengnan Gong; Ziqi Yu; Yujia Luo; Yixiang Zhao; Erfei Xue; Huimin Lu; Di Xiang; Fei Sun (Communications Biology)
Abstract Sleep deprivation (SD) has been demonstrated to cause male reproductive dysfunction; however, its underlying mechanisms remain unclear. In this work, we conduct Mendelian randomization analysis, which indicates a significant association between sleep disorders and male infertility in humans. To explore the potential mechanism, ten-week-old male Sprague-Dawley rats are subjected to continuous SD for five days, showing significantly reduced epididymal sperm concentration and motility compared to the control group. SD treatment also decreases serum testosterone levels and epididymal sperm transit time in male rats. Histological analysis reveals reproductive system damage, while bulk and single-cell RNA sequencing highlight that SD significantly alters transcriptomes and induces differentially expressed genes with significant heterogeneity across three segments of the epididymis. Gene ontology analysis indicates that SD upregulates inflammatory response genes, especially in the more inflammation-sensitive cauda epididymis. Moreover, SD activates immune cells and causes cytokines and chemokines to accumulate in the cauda epididymis. However, recovery sleep mitigates this damage. Our findings reveal that continuous SD disrupts the epididymal immunological microenvironment, lowering sperm quality and potentially contributing to male infertility.